Childhood obesity: Sequelae in adult life (Bangladesh Journal of Medicine, 2023)
Childhood obesity is a growing global health hazard extending to adulthood. The prevalence of obesity in children in developed and developing countries has risen dramatically in the past few decades and is currently at epidemic proportions. Obese children and adolescents were around five times more likely to be obese in adulthood than those who were not obese. Adiposity rebound in early childhood is a risk factor for obesity in adolescence and adulthood. Numerous sequelae are associated with children being overweight or obese, even at a very young age. Obesity in childhood and adolescence is significantly associated with an increased risk of insulin resistance, type 2 diabetes mellitus, dyslipidemia, hypertension, metabolic syndrome, non-alcoholic fatty liver disease, and obstructive sleep apnea. Obese children are more likely to experience psychological morbidity, lower self-esteem, and more behavioral problems than non-obese children. These comorbid conditions may progress to adult life and the development of atherosclerosis, cerebrovascular disorders, and cardiovascular morbidity later in life. Obese children are more likely to become obese adults and suffer lifelong physical and mental problems and risk of premature mortality. The use of infant formula, decreased physical activity, excessive calorie intake, and changes in gut microbiota patterns are associated with the increasing prevalence of childhood obesity. Efforts will be focused on trying to treat obesity itself and, therefore, prevent progression to overt sequelae, either in childhood or later in adult life. The most important strategy for preventing obesity and sequelae is lifestyle modification which includes healthy eating behaviors, regular physical activity, and reduced sedentary activity.Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 191-192